Allgrove's Syndrome: Two Case Reports and Review of Literature - Daniel Zamanfar; Elika Shokri; Shiva Shadani; Soheila Shahmohammadi (Mazandaran University of Medical Sciences, 2015)
Introduction: Allgrove's syndrome (AS) is a rare cause of adrenal insufficiency inherited in an autosomal recessive pattern. Usually the disease is manifested during the first decade of life with severe hypoglycaemia, which can lead to sudden death. Case Presentation: Here we described two cases of Allgrove's syndrome; the first case was an 8-year-old male admitted to hospital for evaluation of seizure and gait abnormality and the second case was a 4-year-old boy admitted for evaluation of hyperpigmentation of his skin and buccal mucosa for eight months, also we made a review of literature. Conclusions: Alacrima is considered to be the earliest clinical manifestation of Triple A syndrome and early recognition of glucocorticoid deficiency would prevent hypoglycaemic convulsions, neurological sequelae and death. A carful replacement of glucocorticoids is critical to avoid adrenal crisis and allow normal growth and development.